A Hedonic Model for Apartment Rentals in Ikeja Area of Lagos Metropolis - Babawale, G.K.; Koleoso, H. A.; Otegbulu, C.A. (Mediterranean Journal of Social Sciences, 2012)
The hedonic pricing model has been employed with a degree of success in housing market analysis in developed countries.This paper demonstrates the potentials of the same technique to the study of housing markets in a developing country like Nigeria. Thepaper used data from Ikeja area of Lagos state, Nigeria, to provide empirical evidence on market parameters that describe the hedonicprice structure for apartments (flats) in a typical Nigerian city. Primary data were elicited through structured questionnaire, complementedwith selective interviews and personal observations. The results revealed that number of bedrooms, condition of the property, availabilityof pipe-borne water, average size of bedrooms, and numbers of bath/toilets, in that order, are the main descriptors of apartment rentalsin the study area. The results of this empirical investigation are of particular importance to investors, developers, financiers, and realestate valuers operating in the property sub-market under consideration. Among others, adequate knowledge of issues investigated andraised would assist developers to build to consumer tastes and preferences. The resulting model also provides an alternative totraditional valuation techniques and affords greater flexibility in accounting for sustainability in real estate valuation.